The Relationship Between Physical Activity of Pregnant Women and the Incident of Low Back Pain during the Third Trimester - Cut Mutiah; Joula Timisela; Cakrawati R Cakrawati R; Fyzria Qudratullah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
ABSTRACT Low back Pain is a common complaint among pregnant women, especially in the third trimester , due to physiological and biomechanical changes during pregnancy. Physical activity is thought to be associated with lower back pain. This study aimed to determine the relationship between physical activity and the incidence of low back pain. back pain during the third trimester . This study used an analytical design with a cross-sectional approach . The study sample consisted of 65 pregnant women in their third trimester selected using a purposive sampling technique. Data were collected through interviews using a physical activity questionnaire and a pain scale. Data analysis used the chi-square test . The results showed that pregnant women with heavy physical activity had a lower incidence of back pain was 72.7%, while light physical activity was 38.5%. The statistical test results showed a p value of 0.014 (p < 0.05). It was concluded that there is a significant relationship between physical activity of pregnant women and the incidence of low blood pressure. back pain during the third trimester Keywords: Physical Activity, Pregnant Women, Low Back Pain , Trimester III